Autoregulatory “Multitasking” at Endothelial Cell Junctions by Junction-Associated Intermittent Lamellipodia Controls Barrier Properties - Seebach, Jochen; Klusmeier, Nadine; Schnittler, Hans (Frontiers in Physiology, 2021)
Abstract Vascular endothelial cell (EC) junctions are key structures controlling tissue homeostasis in physiology. In the last three decades, excellent studies have addressed many aspects of this complex and highly dynamic regulation, including cell signaling, remodeling processes of the proteins of tight junctions, adherens junctions, and gap junctions, the cytoskeleton, and post-transcriptional modifications, transcriptional activation, and gene silencing. In this dynamic process, vascular endothelial cadherin (VE-cadherin) provides the core structure of EC junctions mediating the physical adhesion of cells as well as the control of barrier function and monolayer integrity via remodeling processes, regulation of protein expression and post-translational modifications. In recent years, research teams have documented locally restricted dynamics of EC junctions in which actin-driven protrusions in plasma membranes play a central role. In this regard, our research group showed that the dynamics of VE-cadherin is driven by small (1–5 µm) actin-mediated protrusions in plasma membranes that, due to this specific function, were named “junction-associated intermittent lamellipodia” (JAIL). JAIL form at overlapping, adjacent cells, and exactly at this site new VE-cadherin interactions occur, leading to new VE-cadherin adhesion sites, a process that restores weak or lost VE-cadherin adhesion. Mechanistically, JAIL formation occurs locally restricted (1-5µm) and underlies autoregulation in which the local VE-cadherin concentration is an important parameter. A decrease in the local concentration of VE-cadherin stimulates JAIL formation, whereas an increase in the concentration of VE-cadherin blocks it. JAIL mediated VE-cadherin remodeling at the subjunctional level have been shown to be of crucial importance in angiogenesis, wound healing, and changes in permeability during inflammation. The concept of subjunctional regulation of EC junctions is strongly supported by permeability assays, which can be employed to quantify actin-driven subjunctional changes. In this brief review, we summarize and discuss the current knowledge and concepts of subjunctional regulation in the endothelium.